High-performance conductive AES composite material and preparation method thereof
By using mesoporous indium trioxide/polyaniline materials and niobium pentachloride-modified basic metal salt whiskers to form a conductive network structure, the problem of insufficient conductivity and mechanical properties of AES composite materials was solved, and AES composite materials with high conductivity and strong mechanical properties were realized.
Patent Information
- Application Number
- CN202310951165.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-31
- Publication Date
- 2025-02-14
AI Technical Summary
The current AES composite materials have insufficient electrical conductivity and mechanical properties, which limits their application in the automotive materials field.
Mesoporous indium trioxide/polyaniline material was used as the conductive filler, and the interfacial compatibility was improved by modifying the basic metal salt whiskers with niobium pentachloride to form a conductive network structure. Combined with the hydrogen bonding and protonation effects of phytic acid, the conductivity was enhanced.
The surface resistivity of the prepared AES composite material was significantly reduced to (5.5-7.5)×10⁶Ω, and its mechanical properties were significantly improved, expanding its application range.
Smart Images

Figure BDA0004368461300000021 
Figure BDA0004368461300000151 
Figure BDA0004368461300000161
Abstract
Description
Technical Field
[0001] The invention belongs to the field of polymer materials, and in particular relates to a high-performance conductive AES composite material and a preparation method thereof. Background Art
[0002] Acrylonitrile-EPDM rubber-styrene copolymer (AES) is a widely used polymer resin with various properties similar to ABS, but compared with ABS, it has excellent weather resistance, thermal stability, dimensional stability and toughness, and also has good processability. However, in some automotive material application fields, AES has very high requirements for mechanical properties and electrical conductivity. For example, in electronic connectors, sensors and electric drive systems, AES needs to have good electrical conductivity, and generally requires the surface resistivity of the material to reach 10 6 Ω to ensure the transmission of electrical signals and the normal operation of circuits. Conductive performance requirements usually involve aspects such as the material's volume resistance, surface resistance, and electromagnetic shielding. Currently, this is mainly achieved by adding conductive agents such as carbon black, but the surface resistivity of the final material is higher than 10 7 Ω, which is higher than the requirement. This limits the application of AES composite materials in some specific fields.
[0003] In view of these deficiencies, the present invention innovatively synthesizes a new type of high-performance conductive AES composite material, which has excellent mechanical properties and conductive properties. This AES composite material has not been reported so far, which has very important practical significance for expanding the application field of AES composite materials. Summary of the invention
[0004] In view of this, the present invention innovatively synthesizes a high-performance conductive AES composite material, which has excellent conductive and mechanical properties, and solves the technical problems of limited mechanical properties and conductive capacity of AES in the prior art.
[0005] The objective of the present invention is achieved through the following technical solutions:
[0006] A high-performance conductive AES composite material and a preparation method thereof, which comprises the following components in parts by weight:
[0007]
[0008] The conductive filler is a mesoporous indium trioxide / polyaniline material.
[0009] In a further embodiment, the modified basic metal salt whiskers are niobium pentachloride modified basic metal salt whiskers.
[0010] The preparation method of niobium pentachloride modified basic metal salt whiskers comprises the following steps:
[0011] (1) adding a metal salt to an alkaline solution and reacting the solution in a water bath; filtering, washing, and aging the reaction solution to obtain basic metal salt whiskers;
[0012] (2) adding basic metal salt whiskers, niobium pentachloride and acetone into deionized water for reaction in a water bath; filtering, washing and drying the reaction solution to obtain niobium pentachloride-modified basic metal salt whiskers.
[0013] The reaction equation of basic metal salt whiskers is as follows:
[0014] M 2+ +2OH - →M(OH)2
[0015] M(OH)2+M 2+ +2Cl - →MCl2·M(OH)2
[0016] M represents metal, such as magnesium, copper, etc.
[0017] Preferably, the mass ratio of the metal salt, water and base in step (1) is (30-50):(100-160):(18-24).
[0018] The alkali solution is a sodium hydroxide aqueous solution, a potassium hydroxide aqueous solution or a barium hydroxide aqueous solution;
[0019] The metal salt is magnesium chloride, magnesium sulfate, copper sulfate or copper chloride;
[0020] The reaction in a water bath condition refers to reacting in a water bath at 60-80° C. for 16-20 hours;
[0021] The aging refers to aging in an oven at 70-90°C for 8-12 hours;
[0022] Preferably, the mass ratio of the basic metal salt whiskers, niobium pentachloride, acetone and deionized water in step (2) is (30-40): (4-8): (30-40): (60-80);
[0023] The water bath reaction refers to reacting in a water bath at 70-90°C for 10-16h;
[0024] The drying refers to placing in a drying oven at 70-90°C for 8-12 hours.
[0025] In a further embodiment, the preparation method of the conductive filler mesoporous indium trioxide / polyaniline material comprises the following steps:
[0026] (1) Weigh a certain amount of indium nitrate, ammonia water, and deionized water, put them into a reaction vessel, and react them in a water bath at 60-80° C. for 12-16 hours to obtain solution C;
[0027] (2) Filter solution C, wash it, and dry it in a drying oven at 60-80°C for 10-12 hours to obtain solid D;
[0028] (3) placing solid D in a muffle furnace and calcining at 680-720° C. for 8-12 h to obtain mesoporous indium trioxide;
[0029] (4) Weigh a certain amount of mesoporous indium trioxide, initiator ammonium persulfate, aniline, phytic acid, and deionized water, put them into a reaction vessel, and react them in a water bath at 70-90° C. for 10-16 hours to obtain solution E;
[0030] (5) Filter solution E, wash it, and dry it in a drying oven at 50-70° C. for 16-20 hours to obtain a mesoporous indium trioxide / polyaniline type conductive filler.
[0031] Preferably, the mass ratio of indium nitrate, ammonia water and deionized water in step (1) is (30-40): (28-32): (80-100).
[0032] Preferably, the mass ratio of mesoporous indium trioxide, initiator ammonium persulfate, aniline, phytic acid and deionized water in step (4) is (30-40): (0.3-0.5): (16-20): (30-50): (70-90).
[0033] The initiator is ammonium persulfate, sodium persulfate, benzoyl peroxide or azobisisobutyronitrile;
[0034] The antioxidant is one or a mixture of tris(2,4-di-tert-butyl)phenyl phosphite (referred to as Irganox168), pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate (referred to as Irganox1010) and 1,3,5-trimethyl-2,4,6-(3,5-di-tert-butyl-4-hydroxybenzyl)benzene (referred to as Irganox1330).
[0035] The second invention object of the present invention is to provide a method for preparing the above-mentioned conductive high-performance AES composite material, comprising the following steps:
[0036] (1) weighing 80-100 parts of AES, 10-16 parts of modified basic magnesium chloride whiskers, 8-12 parts of conductive fillers, and 0.1-0.5 parts of antioxidants, mixing and stirring to obtain a mixture;
[0037] (2) adding the mixed material obtained in step (1) into a twin-screw extruder for extrusion granulation to obtain an AES composite material;
[0038] Wherein, the twin-screw extruder includes six temperature zones arranged in sequence, with the temperature of zone one being 200-220°C, the temperature of zone two being 240-260°C, the temperature of zone three being 240-260°C, the temperature of zone four being 240-260°C, the temperature of zone five being 240-260°C, the temperature of zone six being 240-260°C, the temperature of the die head being 240-260°C, and the screw speed being 200-280r / min.
[0039] Compared with the prior art, the present invention has the following beneficial effects:
[0040] (1) The modified basic metal salt whiskers in the present application are basic metal salt whiskers modified with niobium pentachloride, wherein niobium pentachloride is a Lewis acid and is corrosive. It adheres to the surface of the basic metal salt whiskers and can increase the roughness of the surface of the basic metal salt whiskers, thereby increasing the mechanical interlocking between the basic metal salt whiskers and the AES matrix, improving the interface compatibility between the basic metal salt whiskers and the AES matrix, and optimizing the mechanical properties of the AES composite material.
[0041] (2) The present application prepares a mesoporous indium trioxide / polyaniline type conductive filler with a polyaniline gel as a coating layer, which forms a conductive network structure through the polyaniline gel to enhance the conductive properties of AES.
[0042] (3) In the present application, phytic acid is added to the conductive filler, which can generate hydrogen bonds with the In-O groups on the surface of mesoporous indium trioxide, which is beneficial to the uniform dispersion of mesoporous indium trioxide in the AES system. On the other hand, phytic acid has a phosphate group, which can be protonated with the N atoms on the polyaniline chain to promote the formation of the conductive network structure of the polyaniline gel, thereby further enhancing the conductive properties of the AES.
[0043] (4) The AES composite material prepared by the present invention has high electrical conductivity, and its surface resistivity is (5.5-7.5)×10 6 Ω, which is significantly higher than the conductivity of carbon black with conventional conductive agent; it also has strong mechanical properties. DETAILED DESCRIPTION
[0044] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively below in conjunction with specific embodiments. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly understood.
[0045] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0046] The raw materials used in the following examples are as follows:
[0047] AES (model SK50), Japan UMG;
[0048] Magnesium chloride, Jinan Qiwei Chemical Co., Ltd.;
[0049] Sodium hydroxide, Jinan Kunfeng Chemical Co., Ltd.;
[0050] Deionized water, Xiamen Aoquan Environmental Protection Technology Co., Ltd.;
[0051] Niobium pentachloride, Hubei Chengfeng Chemical Co., Ltd.;
[0052] Commercially available basic magnesium chloride whiskers, Shandong Hezhan Chemical Co., Ltd.;
[0053] Acetone, Jinan Wenzhu Chemical Co., Ltd.;
[0054] Ammonium persulfate, Shandong Zhengyu Chemical Co., Ltd.;
[0055] Indium nitrate, Shandong Changyao New Materials Co., Ltd.;
[0056] Ammonia water, Jinan Mengqiao Chemical Co., Ltd.;
[0057] Aniline, Qingdao Jieshikang Biotechnology Co., Ltd.; Phytic acid, Shandong Siyang Biotechnology Co., Ltd.;
[0058] Antioxidant (model Irganox168, Irganox1010, Irganox1330), BASF.
[0059] In the following examples, the mixing was performed using a QD-GJS-B12K high-speed mixer, produced by Beijing Hengaode Instruments Co., Ltd.; the twin-screw extruder was a ZSK30 twin-screw extruder, produced by W&P of Germany.
[0060] Preparation Example 1
[0061] (1) Weigh 300 g of magnesium chloride, 1.0 kg of deionized water, and 180 g of sodium hydroxide, put them into a reaction vessel, and react them in a 60° C. water bath for 16 h to obtain solution A;
[0062] (2) filtering solution A, washing it, and aging it in an oven at 70° C. for 8 h to obtain basic magnesium chloride whiskers;
[0063] (3) Weigh 300 g of basic magnesium chloride whisker, 40 g of niobium pentachloride, 300 g of acetone, and 600 g of deionized water, put them into a reaction vessel, and react them in a 70° C. water bath for 10 h to obtain solution B;
[0064] (4) Filter solution B, wash it, and dry it in a drying oven at 70° C. for 8 h to obtain modified basic magnesium chloride whiskers M1.
[0065] Preparation Example 2
[0066] (1) Weigh 300 g of indium nitrate, 280 g of ammonia water, and 800 g of deionized water, put them into a reaction vessel, and react them in a 60° C. water bath for 12 h to obtain solution C;
[0067] (2) Filter solution C, wash it, and dry it in a drying oven at 60°C for 10 h to obtain solid D;
[0068] (3) placing solid D in a muffle furnace and calcining at 680° C. for 8 h to obtain mesoporous indium trioxide;
[0069] (4) Weigh 300 g of mesoporous indium trioxide, 3 g of initiator ammonium persulfate, 160 g of aniline, 300 g of phytic acid, and 700 g of deionized water, put them into a reaction vessel, and react them in a 70° C. water bath for 10 h to obtain solution E;
[0070] (5) The solution E was filtered, washed, and dried in a drying oven at 50° C. for 16 h to obtain a mesoporous indium trioxide / polyaniline type conductive filler N1.
[0071] Example 1
[0072] (1) Weigh 80 parts of AES, 10 parts of modified basic magnesium chloride whisker M1, 8 parts of conductive filler N1, and 0.1 parts of Irganox 1010, mix and stir to obtain a mixture;
[0073] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain an AES composite material P1.
[0074] The twin-screw extruder comprises six temperature zones arranged in sequence, with the temperature of zone one at 200°C, the temperature of zone two at 240°C, the temperature of zone three at 240°C, the temperature of zone four at 240°C, the temperature of zone five at 240°C, the temperature of zone six at 240°C, the head temperature at 240°C, and the screw speed at 200r / min.
[0075] Preparation Example 3
[0076] (1) Weigh 500 g of magnesium chloride, 1.6 kg of deionized water, and 240 g of sodium hydroxide, put them into a reaction vessel, and react them in a water bath at 80° C. for 20 h to obtain solution A.
[0077] (2) Filter solution A, wash it, and age it in an oven at 90° C. for 12 hours to obtain basic magnesium chloride whiskers.
[0078] (3) Weigh 400 g of basic magnesium chloride whisker, 80 g of niobium pentachloride, 400 g of acetone, and 800 g of deionized water, put them into a reaction vessel, and react them in a 90° C. water bath for 16 h to obtain solution B.
[0079] (4) Filter solution B, wash it, and dry it in a drying oven at 90° C. for 12 h to obtain modified basic magnesium chloride whiskers M2.
[0080] Preparation Example 4
[0081] (1) Weigh 400 g of indium nitrate, 320 g of ammonia water, and 1.0 kg of deionized water, put them into a reaction vessel, and react them in a water bath at 80° C. for 16 h to obtain solution C.
[0082] (2) Filter solution C, wash it, and dry it in a drying oven at 80°C for 12 h to obtain solid D.
[0083] (3) The solid D was placed in a muffle furnace and calcined at 720° C. for 12 h to obtain mesoporous indium trioxide.
[0084] (4) Weigh 400 g of mesoporous indium trioxide, 5 g of initiator ammonium persulfate, 200 g of aniline, 500 g of phytic acid, and 900 g of deionized water, put them into a reaction vessel, and react in a 90° C. water bath for 16 h to obtain solution E.
[0085] (5) The solution E was filtered, washed, and dried in a drying oven at 70° C. for 20 h to obtain a mesoporous indium trioxide / polyaniline type conductive filler N2.
[0086] Example 2
[0087] (1) Weigh 100 parts of AES, 16 parts of modified basic magnesium chloride whisker M2, 12 parts of conductive filler N2, 0.1 parts of antioxidant Irganox 1010, 0.2 parts of antioxidant Irganox 168, and 0.2 parts of antioxidant Irganox 1330, mix and stir to obtain a mixture;
[0088] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain an AES composite material P2.
[0089] The twin-screw extruder includes six temperature zones arranged in sequence, with the temperature of zone one at 220°C, the temperature of zone two at 260°C, the temperature of zone three at 260°C, the temperature of zone four at 260°C, the temperature of zone five at 260°C, the temperature of zone six at 260°C, the head temperature at 260°C, and the screw speed at 280r / min.
[0090] Preparation Example 5
[0091] (1) Weigh 400 g of magnesium chloride, 1.3 kg of deionized water, and 210 g of sodium hydroxide, put them into a reaction vessel, and react them in a 70° C. water bath for 18 h to obtain solution A.
[0092] (2) Filter solution A, wash it, and age it in an oven at 80° C. for 10 h to obtain basic magnesium chloride whiskers.
[0093] (3) Weigh 350 g of basic magnesium chloride whisker, 60 g of niobium pentachloride, 350 g of acetone, and 700 g of deionized water, put them into a reaction vessel, and react them in a water bath at 80° C. for 13 h to obtain solution B.
[0094] (4) Filter solution B, wash it, and dry it in a drying oven at 80° C. for 10 h to obtain modified basic magnesium chloride whiskers M3.
[0095] Preparation Example 6
[0096] (1) Weigh 350 g of indium nitrate, 300 g of ammonia water, and 900 g of deionized water, put them into a reaction vessel, and react them in a 70° C. water bath for 14 h to obtain solution C.
[0097] (2) Solution C was filtered, washed, and dried in a drying oven at 70°C for 11 h to obtain solid D.
[0098] (3) Solid D is placed in a muffle furnace and calcined at 700° C. for 10 h to obtain mesoporous indium trioxide.
[0099] (4) 350 g of mesoporous indium trioxide, 4 g of initiator ammonium persulfate, 180 g of aniline, 400 g of phytic acid, and 800 g of deionized water were weighed and placed in a reaction vessel, and reacted in a water bath at 80° C. for 13 h to obtain a solution E.
[0100] (5) The solution E was filtered, washed, and dried in a drying oven at 60° C. for 180 h to obtain a mesoporous indium trioxide / polyaniline type conductive filler N3.
[0101] Example 3
[0102] (1) Weigh 90 parts of AES, 13 parts of modified basic magnesium chloride whisker M3, 10 parts of conductive filler N3, 0.1 parts of antioxidant Irganox 168, and 0.2 parts of antioxidant Irganox 1010, mix and stir to obtain a mixture;
[0103] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain an AES composite material P3.
[0104] The twin-screw extruder includes six temperature zones arranged in sequence, with the temperature of zone one at 215°C, the temperature of zone two at 255°C, the temperature of zone three at 255°C, the temperature of zone four at 255°C, the temperature of zone five at 255°C, the temperature of zone six at 255°C, the head temperature at 255°C, and the screw speed at 245r / min.
[0105] Preparation Example 7
[0106] (1) Weigh 385 g of copper sulfate, 1.55 kg of deionized water, and 215 g of potassium hydroxide into a reaction vessel, and react in a 75° C. water bath for 19 h to obtain solution A.
[0107] (2) Solution A is filtered, washed, and aged in an oven at 85° C. for 11 h to obtain basic copper sulfate whiskers.
[0108] (3) Weigh 365 g of basic copper sulfate whiskers, 75 g of niobium pentachloride, 385 g of acetone, and 765 g of deionized water, put them into a reaction vessel, and react them in a water bath at 85° C. for 15 h to obtain solution B.
[0109] (4) Solution B was filtered, washed, and dried in a drying oven at 85° C. for 9 h to obtain modified basic copper sulfate whiskers M4.
[0110] Preparation Example 8
[0111] (1) Weigh 335 g of indium nitrate, 315 g of ammonia water, and 885 g of deionized water, put them into a reaction vessel, and react them in a 75° C. water bath for 15 h to obtain solution C.
[0112] (2) Solution C was filtered, washed, and dried in a drying oven at 65°C for 11 h to obtain solid D.
[0113] (3) Solid D was placed in a muffle furnace and calcined at 715° C. for 9 h to obtain mesoporous indium trioxide.
[0114] (4) Weigh 365 g of mesoporous indium trioxide, 4.5 g of initiator sodium persulfate, 195 g of aniline, 465 g of phytic acid, and 865 g of deionized water, put them into a reaction vessel, and react them in a water bath at 85° C. for 15 h to obtain solution E.
[0115] (5) Solution E was filtered, washed, and dried in a drying oven at 65° C. for 18 h to obtain a mesoporous indium trioxide / polyaniline type conductive filler N4.
[0116] Example 4
[0117] (1) Weigh 85 parts of AES, 14 parts of modified basic magnesium chloride whisker M4, 11 parts of conductive filler N4, 0.1 parts of antioxidant Irganox 1010, and 0.2 parts of antioxidant Irganox 1330, mix and stir to obtain a mixture;
[0118] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain an AES composite material P4.
[0119] The twin-screw extruder includes six temperature zones arranged in sequence, with zone one at 215°C, zone two at 245°C, zone three at 245°C, zone four at 245°C, zone five at 245°C, zone six at 245°C, die head temperature at 245°C, and screw speed at 245r / min.
[0120] Preparation Example 9
[0121] (1) Weigh 425 g of magnesium chloride, 1.55 kg of deionized water, and 235 g of sodium hydroxide, put them into a reaction vessel, and react them in a 75° C. water bath for 16 h to obtain solution A.
[0122] (2) Filter solution A, wash it, and age it in an oven at 85° C. for 11 hours to obtain basic magnesium chloride whiskers.
[0123] (3) Weigh 385 g of basic magnesium chloride whiskers, 75 g of niobium pentachloride, 395 g of acetone, and 785 g of deionized water, put them into a reaction vessel, and react them in a water bath at 85° C. for 15 h to obtain solution B.
[0124] (4) Solution B was filtered, washed, and dried in a drying oven at 85° C. for 11 h to obtain modified basic magnesium chloride whiskers M5.
[0125] Preparation Example 10
[0126] (1) Weigh 335 g of indium nitrate, 315 g of ammonia water, and 995 g of deionized water, put them into a reaction vessel, and react them in a 68° C. water bath for 15 h to obtain solution C.
[0127] (2) Solution C was filtered, washed, and dried in a drying oven at 65°C for 12 h to obtain solid D.
[0128] (3) Solid D was placed in a muffle furnace and calcined at 715° C. for 11 h to obtain mesoporous indium trioxide.
[0129] (4) Weigh 395 g of mesoporous indium trioxide, 3.5 g of initiator ammonium persulfate, 195 g of aniline, 485 g of phytic acid, and 855 g of deionized water, put them into a reaction vessel, and react them in a water bath at 85° C. for 15 h to obtain solution E.
[0130] (5) Solution E was filtered, washed, and dried in a drying oven at 65° C. for 19 h to obtain a mesoporous indium trioxide / polyaniline type conductive filler N5.
[0131] Example 5
[0132] (1) Weigh 95 parts of AES, 14 parts of modified basic magnesium chloride whisker M5, 11 parts of conductive filler N5, 0.1 parts of antioxidant Irganox 1010, and 0.1 parts of antioxidant Irganox 168, mix and stir to obtain a mixture;
[0133] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain an AES composite material P5.
[0134] The twin-screw extruder includes six temperature zones arranged in sequence, with the temperature of zone one at 215°C, the temperature of zone two at 255°C, the temperature of zone three at 255°C, the temperature of zone four at 255°C, the temperature of zone five at 255°C, the temperature of zone six at 255°C, the head temperature at 255°C, and the screw speed at 255r / min.
[0135] Comparative Example 1
[0136] (1) Weigh 95 parts of AES, 14 parts of commercially available basic magnesium chloride whiskers, 0.1 parts of antioxidant Irganox 1010, and 0.1 parts of antioxidant Irganox 168, mix and stir to obtain a mixture;
[0137] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain an AES composite material D1.
[0138] The twin-screw extruder includes six temperature zones arranged in sequence, with the temperature of zone one at 215°C, the temperature of zone two at 255°C, the temperature of zone three at 255°C, the temperature of zone four at 255°C, the temperature of zone five at 255°C, the temperature of zone six at 255°C, the head temperature at 255°C, and the screw speed at 255r / min.
[0139] Comparative Example 2
[0140] (1) Weigh 95 parts of AES, 14 parts of modified basic magnesium chloride whisker M5 prepared in Preparation Example 9, 11 parts of conductive carbon black, 0.1 parts of antioxidant Irganox 1010, and 0.1 parts of antioxidant Irganox 168, mix and stir to obtain a mixture;
[0141] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain an AES composite material D2.
[0142] The twin-screw extruder includes six temperature zones arranged in sequence, with the temperature of zone one at 215°C, the temperature of zone two at 255°C, the temperature of zone three at 255°C, the temperature of zone four at 255°C, the temperature of zone five at 255°C, the temperature of zone six at 255°C, the head temperature at 255°C, and the screw speed at 255r / min.
[0143] Comparative Example 3
[0144] (1) Weigh 95 parts of AES, 14 parts of commercially available basic magnesium chloride whiskers, 11 parts of mesoporous indium trioxide / polyaniline conductive filler N5 prepared in Preparation Example 10, 0.1 parts of antioxidant Irganox 1010, and 0.1 parts of antioxidant Irganox 168, mix and stir to obtain a mixture;
[0145] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain an AES composite material D3.
[0146] The twin-screw extruder includes six temperature zones arranged in sequence, with the temperature of zone one at 215°C, the temperature of zone two at 255°C, the temperature of zone three at 255°C, the temperature of zone four at 255°C, the temperature of zone five at 255°C, the temperature of zone six at 255°C, the head temperature at 255°C, and the screw speed at 255r / min.
[0147] The AES composite materials prepared in the above Examples 1-5 and Comparative Examples 1-2 were made into test strips using an injection molding machine. The test data are shown in the following table:
[0148]
[0149]
[0150] In summary, the mechanical properties and conductive properties of Examples 1-5 are generally better than those of Comparative Example 1, the conductive properties are better than those of Comparative Example 2, and the mechanical properties are better than those of Comparative Example 3. This shows that the AES composite material prepared by the method provided by the present invention has excellent mechanical properties and conductive properties, and the application field of the AES composite material can be expanded.
[0151] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0152] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A high performance conductive AES composite material, characterized by: It is composed of the following components by weight: The conductive filler is a mesoporous indium trioxide / polyaniline material.
2. A high performance conductive AES composite material according to claim 1, characterized in that: The modified basic metal salt whiskers are niobium pentachloride modified basic metal salt whiskers.
3. A high performance conductive AES composite material according to claim 2, characterized in that: The method for preparing the niobium pentachloride modified basic metal salt whiskers comprises the following steps: (1) adding a metal salt to an alkaline solution and reacting the solution in a water bath; filtering, washing, and aging the reaction solution to obtain basic metal salt whiskers; (2) adding basic metal salt whiskers, niobium pentachloride and acetone into deionized water for reaction in a water bath; filtering, washing and drying the reaction solution to obtain niobium pentachloride-modified basic metal salt whiskers.
4. A high performance conductive AES composite material according to claim 3, characterized in that: The alkali solution in step (1) is a sodium hydroxide aqueous solution, a potassium hydroxide aqueous solution or a barium hydroxide aqueous solution, and the mass ratio of the metal salt, water and alkali is (30-50): (100-160): (18-24); The reaction in a water bath condition refers to reacting in a water bath at 60-80° C. for 16-20 hours; The aging refers to aging in an oven at 70-90°C for 8-12 hours; The metal salt is magnesium chloride, magnesium sulfate, copper sulfate or copper chloride.
5. A high performance conductive AES composite material according to claim 3, characterized in that: The mass ratio of the basic metal salt whiskers, niobium pentachloride, acetone and deionized water in step (2) is (30-40): (4-8): (30-40): (60-80); The water bath reaction refers to reacting in a water bath at 70-90°C for 10-16h; The drying refers to placing in a drying oven at 70-90°C for 8-12 hours.
6. A high performance conductive AES composite material according to claim 1, characterized in that: The preparation method of the mesoporous indium trioxide / polyaniline material comprises the following steps: (1) adding indium nitrate to an aqueous ammonia solution, reacting in a water bath, and filtering, washing, and drying the reaction solution to obtain a solid reactant; (2) calcining the solid reactant at high temperature to obtain mesoporous indium trioxide; (3) adding mesoporous indium trioxide, an initiator, aniline, and phytic acid into deionized water for reaction in a water bath; and filtering, washing, and drying the reaction solution to obtain a mesoporous indium trioxide / polyaniline material.
7. A high performance conductive AES composite material according to claim 6, characterized in that: The mass ratio of indium nitrate, ammonia water and deionized water in step (1) is (30-40): (28-32): (80-100); The water bath reaction refers to reacting in a water bath at 60-80°C for 12-16h; The drying step is to place the mixture in a drying oven at 60-80°C for 10-12 hours.
8. A high performance conductive AES composite material according to claim 6, characterized in that: In step (2), the high temperature calcination is performed by placing the solid reactants in a muffle furnace and calcining at 680-720° C. for 8-12 hours. The mass ratio of mesoporous indium trioxide, initiator, aniline, phytic acid and deionized water in step (3) is (30-40): (0.3-0.5): (16-20): (30-50): (70-90); The initiator is ammonium persulfate, sodium persulfate, benzoyl peroxide or azobisisobutyronitrile; The water bath reaction refers to reacting in a water bath at 70-90°C for 10-16h; The drying step is to place the mixture in a drying oven at 50-70°C for 16-20 hours.
9. A high performance conductive AES composite material according to claim 1, characterized in that: The antioxidant is one of tris(2,4-di-tert-butyl)phenyl phosphite, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate and 1,3,5-trimethyl-2,4,6-(3,5-di-tert-butyl-4-hydroxybenzyl)benzene or a mixture of several thereof.
10. The method for preparing a high-performance conductive AES composite material according to claim 1, characterized in that: The following steps are involved: (1) Weigh 80-100 parts of AES, 10-16 parts of modified basic metal salt whiskers, 8-12 parts of conductive fillers, and 0.1-0.5 parts of antioxidants, mix and stir to obtain a mixture; (2) adding the mixed material obtained in step (1) into a twin-screw extruder for extrusion granulation to obtain an AES composite material; The twin-screw extruder includes six temperature zones arranged in sequence, with the temperature of zone one being 200-220°C, the temperature of zone two being 240-260°C, the temperature of zone three being 240-260°C, the temperature of zone four being 240-260°C, the temperature of zone five being 240-260°C, the temperature of zone six being 240-260°C, the temperature of the die head being 240-260°C, and the screw speed being 200-280r / min.